2014
DOI: 10.2494/photopolymer.27.639
|View full text |Cite
|
Sign up to set email alerts
|

Novel EUV Resists Materials for 16nm HP and beyond

Abstract: Extreme ultraviolet (EUV) lithography is a candidate for the manufacturing of semiconductor devices at the 22 nm half pitch node and below. EUV lithography requires high performance resist with limited outgassing property. The key challenge for EUV resist is the simultaneous requirement of ultrahigh resolution (R), low line edge roughness (L) and high sensitivity (S) for lines and spaces (LS) features. To achieve high sensitivity, containing fluorine atom is one of the popular methods because the fluorine atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…Combined with photoradical initiator or PAG, these NP gave both positive and negative tone patterns. The best result was obtained from methacryl acid (MAA) or trans-2, 3-dimethylacrylic acid (DMA) ligated ZrO 2 -NP with PAG enabling sub 30 nm line patterns at an EUV dose below 5 mJ/cm 2 , showing one of the best EUV sensitivity results ever reported. It was assumed that ligand exchange from weaker acid (MAA, DMA) to stronger acid from PAG (benzoic acid, sulfonic acid etc.)…”
Section: Metal Oxide Nanoparticles (Np)mentioning
confidence: 76%
See 2 more Smart Citations
“…Combined with photoradical initiator or PAG, these NP gave both positive and negative tone patterns. The best result was obtained from methacryl acid (MAA) or trans-2, 3-dimethylacrylic acid (DMA) ligated ZrO 2 -NP with PAG enabling sub 30 nm line patterns at an EUV dose below 5 mJ/cm 2 , showing one of the best EUV sensitivity results ever reported. It was assumed that ligand exchange from weaker acid (MAA, DMA) to stronger acid from PAG (benzoic acid, sulfonic acid etc.)…”
Section: Metal Oxide Nanoparticles (Np)mentioning
confidence: 76%
“…It is believed that higher Tg polymer is favorable to suppress acid diffusion which deteriorates resolution and LWR. Sakai et al reported that 13% increase of polymer Tg lead LWR improvement from 5.9 nm to 3.9 nm in 22 nm HP [2]. While sensitivity became slightly worse, the total resist performance turned out improved, judged from the Z-factor [3].…”
Section: Pag Blend Type 211 Polymer Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant improvement in the resolution has been expected for EUV lithography because of the reduction in the wavelength. The resolution of EUV lithography with chemically amplified resist processes has already reached the sub-16-nm region [5,6]. The focus of the resist development is shifting to the 11-nm half-pitch node.…”
Section: Introductionmentioning
confidence: 99%
“…3) The development of chemically amplified resists capable of 11-nm-half-pitch fabrication is ongoing. 4,5) Also, high NA exposure tools have recently attracted much attention. 6) The resolution of the optical image will be significantly improved.…”
Section: Introductionmentioning
confidence: 99%